2020
DOI: 10.1155/2020/3542613
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin Inhibits Glioblastoma Proliferation through the AKT/mTOR Pathway and Induces Autophagy

Abstract: Purpose. Arctigenin (ARG) is a natural lignan compound extracted from Arctium lappa and has displayed anticancer function and therapeutic effect in a variety of cancers. Arctigenin is mainly from Arctium lappa extract. It has been shown to induce autophagy in various cancers. However, as for whether arctigenin induces autophagy in gliomas or not, the specific mechanism is still worth exploring. Methods. Using CCK8, the monoclonal experiment was made to detect the proliferation ability. The scratch experiment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Downstream, Akt upregulates the mammalian target of rapamycin (mTOR) and nuclear factor κappa of activated B cells (NF-κB), which induce proliferation. However, arctigenin, curcumin, diosgenin, and berberine downregulate (p-)mTOR, while diosgenin downregulates NF-κB [ 29 , 54 , 61 ]. Moreover, galbanic acid exerts antiproliferative, anti-metastatic, and pro-apoptotic effects via PI3K/Akt/mTOR signaling, while N45, a natural steroidal saponin, upregulates apoptosis through ROS/PI3K/Akt signaling in TMZ-resistant GBM cells [ 65 , 66 ].…”
Section: Mechanistic Effects Of Natural Compounds On Glioblastomamentioning
confidence: 99%
See 2 more Smart Citations
“…Downstream, Akt upregulates the mammalian target of rapamycin (mTOR) and nuclear factor κappa of activated B cells (NF-κB), which induce proliferation. However, arctigenin, curcumin, diosgenin, and berberine downregulate (p-)mTOR, while diosgenin downregulates NF-κB [ 29 , 54 , 61 ]. Moreover, galbanic acid exerts antiproliferative, anti-metastatic, and pro-apoptotic effects via PI3K/Akt/mTOR signaling, while N45, a natural steroidal saponin, upregulates apoptosis through ROS/PI3K/Akt signaling in TMZ-resistant GBM cells [ 65 , 66 ].…”
Section: Mechanistic Effects Of Natural Compounds On Glioblastomamentioning
confidence: 99%
“…Downstream, cytochrome c, Bad, and Bim promote the activation of caspase 9, which in turn activates caspase 3. A blockade of Akt/mTOR signaling mediated by arctigenin or osthole enhances the activity of Beclin-1, which supports caspase 3 activation [ 61 , 64 ]. Caspase 3 specifically blocks the inhibitor of caspase-activated DNAse (ICAD), allowing CAD to cause DNA fragmentation—an effect observed after diosgenin application [ 54 ].…”
Section: Mechanistic Effects Of Natural Compounds On Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons why we focused our interest on EGFR-PI3K-AKT-mTOR signaling pathway is that our previous investigation, using Array Comparative Genomic Hybridization (aCGH) and bioinformatics utilizing a Bioconductor package, Genomic Identification of Significant Targets in Cancer (GISTIC) 2.0.23 and DAVID software, identified main actors of the PI3K-AKT pathway activated in human astrocytomas and suggested that DNA copy number alterations play important roles in its etiology and progression [ 7 ]. Furthermore, the AKT signaling pathway mediates cell regulation, cell proliferation, cell cycle, and carbohydrate metabolism by further phosphorylation of GSK3β (glycogen synthase kinase 3 beta), Bad (bcl-2 bound death promoter), caspase-9, NF-κB (nuclear factor κB), mTOR (target molecule of rapamycin in mammals) and p21 protein [ 8 , 9 , 10 , 11 , 12 , 13 ]. Since recent studies have revealed the essential role of EGFR-PI3K-AKT-mTOR signaling in human tumors [ 14 ], we were interested in the molecular characteristics of this pathway across the three pathohistological types and grades of diffuse brain gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicated that inhibiting the ETV4/EMP1 signaling axis may play an important role in promoting autophagy and apoptosis in LN-229 GBM cells. mTOR has been reported to be upregulated in GBM, and the PI3K/AKT/mTOR signaling pathway was discovered to play a crucial role in regulating cell proliferation, apoptosis and autophagy (22). In the present study, LN-229 cells were co-incubated with RAP, si-ETV4 and Oe-EMP1 alone or in combination, and the expression levels of p-AKT and p-mTOR, which indicate that the PI3K/AKT/mTOR signaling pathway has been activated, were measured.…”
Section: Discussionmentioning
confidence: 99%